DETEKSI DINI FAKTOR RESIKO PTM PADA REMAJA BERBASIS POSBINDU - Sri Noor Mintarsih; Ria Ambarwati; Ana Yuliah Rahmawati; Mardiana Mardiana (Poltekkes Kemenkes Semarang, 2022)
Background: PTM is currently a risk for all people, including the youth group. a trigger factor for the emergence of PTM in adolescents is a sedentary lifestyle and unhealthy eating behavior, namely liking modern foods that are high in fat and low in fiber, lack of fruit and vegetable consumption, lack of activity and exercise, increased stressors and exposure to environmental conditions that are not conducive to health. Posbindu in schools as an effort to monitor and early detect NCD risk factors in students.Objective: To examine risk factors for adolescent NCDs in schools by empowering Peer Counselors through the implementation of Basic Posbindu in schools.Method: This type of cross-sectional research with a survey approach to students at SMAN XI and XV as many as 241 students. Peer counselors who were trained to become Posbindu cadres (63 students) to conduct early detection of NCD risk factors in their friends. PTM Risk Factor Detection usingPTM Risk Factor Monitoring Card includes personal identity, history of non-communicable diseases, behavioral risk factors, and physical examination by peer counselors and officers from the health center. Descriptive analysis was in the form of PTM risk factor proportions.Results: The behavioral risk factors found were a lack of consuming vegetables and fruit 77.4%, consuming excessive sweet food 92.8%, consuming excessive salty food 84.8%, consuming excessive fatty food 5.9%, consuming alcohol 0.5% and smoking habits 5.9% as well as lack of physical activity 69.7%. The proportion of adolescents who are overweight is 36.1%, high blood pressure is 43.0% and high sugar content is 23.0%.Conclusion: Lack of consuming vegetables and fruit, excessively sweet foods, excessively salty foods, lack of physical activity, obesity, high blood pressure, and high sugar levels are risk factors for PTM in adolescents at school. Early Detection of PTM Risk Factors in adolescents based on Posbindu can be done by Peer Counselors in the environment School.